2018
DOI: 10.3389/fmicb.2018.03004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biofilms Formed by Foodborne Methicillin-Resistant Staphylococcus aureus

Abstract: The objective of this study was to evaluate the capacity of 49 methicillin resistant Staphylococcus aureus (MRSA) from foods of animal origin (42 from dairy products and 7 from meat and meat products) to form biofilms. Overall, a higher biofilm biomass was observed for those MRSA strains harboring SCCmec type IV, while 8 MRSA strains (5 from dairy products and 3 from meat and meat products) were classified as strong biofilm formers in standard Tryptic Soy Broth medium. When a prolonged incubation period (48 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 42 publications
3
19
0
1
Order By: Relevance
“…In this study, all isolates from food showed higher biofilm production than those from humans (52.6%) and sheep mastitis cases (17.9%). This result was in concordance with the study of Rodriguez-Lazaro et al [38]. Most of S. aureus isolates from sheep mastitis did not form biofilms (82.1%), which was in concordance with a previous report on S. aureus isolates from sheep milk [39].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, all isolates from food showed higher biofilm production than those from humans (52.6%) and sheep mastitis cases (17.9%). This result was in concordance with the study of Rodriguez-Lazaro et al [38]. Most of S. aureus isolates from sheep mastitis did not form biofilms (82.1%), which was in concordance with a previous report on S. aureus isolates from sheep milk [39].…”
Section: Discussionsupporting
confidence: 93%
“…After 15 min of dyeing, the excess CV was removed by washing twice with sterile water. Eventually, the fixed CV was released by 33% acetic acid and the absorbance detection at 595 nm was measured 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Biofilms are heterogeneous groupings of microorganisms sticking to a surface, included within a polymer matrix secreted by the microorganisms themselves and made up principally of polysaccharides, proteins and nucleic acids 15,16 . This matrix acts as a physical barrier against chemical agents and provides a protective ecological niche enhancing the survival of the microorganisms.…”
Section: Introductionmentioning
confidence: 99%